Diseño de una planta para la producción de nitrato de amonio por el proceso uhde. - Alvitez Ruíz, Silvia Elizabeth (2015)
This thesis is a technical and economic study to demonstrate the feasibility of installing a plant to produce ammonium nitrate fertilizer in Ilo- Peru. This research covers market research, plant design, economic evaluation and environmental assessment. The rationale for this project is the current demand for the product in question. It has also taken into account the agro-industrial development by facing the country. The plant capacity is set at 20 000 tonnes / year by UHDE process which has superior properties compared to other processes, facilities will be located in Ilo, Moquegua. This project requires an investment of $ 8 215 284,85 including fixed capital and working capital, investment will be recovered in 2.7 years as long as they produce 100% of the installed capacity with an after-tax IRR of 15,1%. The environmental impacts are evaluated by determining required to treat effluents contain high loads of nitrogen and the emissions exceed the maximum permissible limits for particulate matter (PM10), for this is included in the design of an internal filter bag for retention particles and a reactor system nitrification-denitrification (SHARON process) to reduce the nitrogen concentration up to 10 ppm (Supreme Decree No. 002-2008-MINAM).